1980
DOI: 10.1111/j.1399-0004.1980.tb02293.x
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic occurrence of Duchenne Muscular Dystrophy: evidence for new mutation

Abstract: The mechanism of inheritance of sporadically occurring Duchenne muscular dystrophy has been investigated in 42 families, using carrier detection methods and genetic evaluation. Our studies find that serum CPK detects 72 % of female carriers of DMD. Quantitative LDH and/or its isozymes were not found to be a useful means of carrier detection, as reported by Roses et al. (1977). Employing family pedigree data and CPK carrier testing, we determined by Bayesian methods the probability that the mother and maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…The certainty of being a DMD carrier was 95%, so there is a 5% chance that the mutation would not be linked to the at‐risk haplotype because of a recombination event.In families 4(III1 and III2) and 11(III1), each with a sporadic case, the fetus and the DMD patients shared the same haplotype, thus the risk of inheriting the maternal mutation would be 67%, because two thirds of DMD cases are transmitted. This would be approximately the probability of the fetuses being carriers 1, 2 Families with a non‐informative or inconclusive diagnosis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The certainty of being a DMD carrier was 95%, so there is a 5% chance that the mutation would not be linked to the at‐risk haplotype because of a recombination event.In families 4(III1 and III2) and 11(III1), each with a sporadic case, the fetus and the DMD patients shared the same haplotype, thus the risk of inheriting the maternal mutation would be 67%, because two thirds of DMD cases are transmitted. This would be approximately the probability of the fetuses being carriers 1, 2 Families with a non‐informative or inconclusive diagnosis .…”
Section: Resultsmentioning
confidence: 99%
“…DMD is the most common X‐linked recessive lethal disorder with an incidence of ∽1 in 3500 newborns. Approximately one third of the cases result from de novo mutations in the dystrophin gene located at the Xp21 region 1–4. Intragenic deletions and duplications together account for over two thirds of the mutations that cause DMD/BMD; the remaining cases are due to point mutations or small insertions/deletions distributed along the entire gene 5.…”
mentioning
confidence: 99%
“…A recent study in which point mutations identified by sequence analysis were likely over represented found an incidence of only 43% deletions, 11% duplications, and 46% point mutations (Flanigan et al 2009). While DMD classically demonstrates a strong family history, about one third of cases occur due to new mutations (Caskey et al 1980). …”
Section: Introductionmentioning
confidence: 99%
“…Findings since that date have been controversial, with a similar frequency being reported by some authors 21 but a higher 22 or lower frequency (around 20%) 23 by others. A sporadic mutation was detected in 16.7% of the present series of DMD/BMD patients.…”
Section: Discussionmentioning
confidence: 78%
“…It has been known since 1987 that DMD/BMD is caused by mutations of the DMD gene, the largest known human gene (2.4 Mb and 79 exons) 20, 21. The recently developed MLPA assay 14, 15 allows deletions and duplications to be detected in any of the 79 exons of this gene.…”
Section: Discussionmentioning
confidence: 99%